2016
DOI: 10.3748/wjg.v22.i40.8967
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an oral iron chelator, deferasirox, on advanced hepatocellular carcinoma

Abstract: AIMTo evaluate the inhibitory effects of deferasirox (DFX) against hepatocellular carcinoma (HCC) through basic and clinical studies.METHODSIn the basic study, the effect of DFX was investigated in three hepatoma cell lines (HepG2, Hep3B, and Huh7), as well as in an N-nitrosodiethylamine-induced murine HCC model. In the clinical study, six advanced HCC patients refractory to chemotherapy were enrolled. The initial dose of DFX was 10 mg/kg per day and was increased by 10 mg/kg per day every week, until the maxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 30 publications
(40 reference statements)
1
36
0
Order By: Relevance
“…We also observed increased FTH protein expression in the tissue sections of patients with cervical cancer (Figure S1 b). The increase in serum ferritin levels in patients with cervical cancer is in accordance with a previous report [28][29][30]. These results con rmed that the occurrence and development of cervical cancer is related to changes in iron metabolism.…”
Section: Discussionsupporting
confidence: 92%
“…We also observed increased FTH protein expression in the tissue sections of patients with cervical cancer (Figure S1 b). The increase in serum ferritin levels in patients with cervical cancer is in accordance with a previous report [28][29][30]. These results con rmed that the occurrence and development of cervical cancer is related to changes in iron metabolism.…”
Section: Discussionsupporting
confidence: 92%
“…DFX was effective against leukemia cells in preclinical studies and because leukemia patients receive repeated blood transfusions, DFX offers a dual benefit as an anti-cancer agent and treatment for iron overload complications. Additionally, DFO and DFX are effective in preclinical studies of pancreatic (193), breast (194), liver (183), gastric (195), and esophageal (196) cancers, and because they are well-characterized they are often used as positive controls for the study of other iron modulators. Despite promising preclinical results, a pilot study of DFX in advanced hepatocellular carcinoma patients found doselimiting toxicities and the majority (4/5) of the patient tumors progressed while on treatment, therefore the efficacy of DFX for the treatment of solid tumors remains questionable (183).…”
Section: Iron Chelationmentioning
confidence: 99%
“…Thus, iron chelation therapy is expected to be a novel strategy for cancer therapy and prevention, particularly oral iron chelators compared to intravenous iron chelators due to their practicability. However, iron chelators cause potentially severe side effects, which makes them difficult to use in some cancer patients [ 22 ]. One study reported that all six hepatocellular carcinoma patients treated with DFX had side effects that led to rhabdomyolysis (increased creatinine kinase activity) or anorexia.…”
Section: Discussionmentioning
confidence: 99%